TANGGUNG JAWAB HUKUM DALAM PELIMPAHAN WEWENANG BEDA PROFESI KESEHATAN - Dipo Pramudito; Gunawan Widjaja (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
Doctors to population ration in Indonesia is the lowest among Southeast Asia Nation. Especially when considering the vast territory in Indonesia, including the geographical form of an archipelagic country. The uneven distribution of doctors throughout Indonesia is a problem in itself. In an effort to improve the health status of citizens, health services must still be carried out, one of which is through the delegation of authority from doctors to health workers such as nurses and midwives. However, this is not without problems. Lack of knowledge of medical and health personnel related to the legal aspects of the delegation of authority is prone to causing conflicts both between doctors and nurses and with patients. The purpose of this study is to understand the legal consequences of the delegation of authority between medical and health personnel. This research is normative juridical research with data sources from primary legal materials such as legislation, and secondary legal materials such as journals and books. This research is also multi-disciplinary in which management science is involved. The result of this research is that the delegation of authority is a form of engagement in which both parties are obliged to fulfill the achievement. In the delegation of mandated authority, authority remain has responsibilities according to cascade liability theory if recipient of the mandate does not violate the agreement. However, recipients are also required to fulfill achievements such as carrying out tasks according to their competence boundaries. Suggestions from this study are that each health facility makes standard operating procedures for delegation of authority and makes a format for delegation of authority.